2018
DOI: 10.1371/journal.pone.0204499
|View full text |Cite
|
Sign up to set email alerts
|

Preventative effects of resveratrol and estradiol on streptozotocin-induced diabetes in ovariectomized mice and the related mechanisms

Abstract: Resveratrol, a non-flavonoid polyphenolic compound, is structurally and functionally similar to estrogen and has drawn great attention for its potentially beneficial effects on diabetes. However, it is not known whether it shares the same protective effect against diabetes as estrogen and the underlying mechanisms. The aim of the present study was to investigate the protective effects of phytoestrogen resveratrol and exogenous 17β-estradiol against streptozotocin (STZ)-induced type 1 diabetes. Female mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 57 publications
1
11
0
2
Order By: Relevance
“…The major factors contributing to T1D-related hyperglycemia are reduced or no insulin secretion, decreased glucose utilization by the peripheral tissue, and increased glucose production. Resveratrol has been shown to improve all of the factors mentioned above in the setting of T1D, as reported by previous preclinical studies [18][19][20][21][22]. In this current study, we also observed that resveratrol treatment significantly reduced FBS and HbA1c in T1D patients.…”
Section: Discussionsupporting
confidence: 89%
“…The major factors contributing to T1D-related hyperglycemia are reduced or no insulin secretion, decreased glucose utilization by the peripheral tissue, and increased glucose production. Resveratrol has been shown to improve all of the factors mentioned above in the setting of T1D, as reported by previous preclinical studies [18][19][20][21][22]. In this current study, we also observed that resveratrol treatment significantly reduced FBS and HbA1c in T1D patients.…”
Section: Discussionsupporting
confidence: 89%
“…It was previously shown that estradiol injections reduced fasting blood GLU levels in non-obese C57BL/6N mice with short-term ovariectomy, while AMPK was activated and gluconeogenic gene expression was reduced in liver tissues [31]. A 4-week subcutaneous injection of estradiol to ovariectomized female mice with STZinduced type 1 diabetes significantly suppressed blood GLU level and increased plasma insulin, suggesting protective effects of estradiol against STZ-induced diabetes [32]. Besides estradiol, various components were identified from DT sap, such as caryophyllene oxide, curcumene, 3, 5-di-tert-butyl-4-hydroxybenzaldehyde, trenbolone, farnesol, dienogest, 2-Hydroxyestradiol, isotretinoin, linoleic acid and costunolide (Table 1).…”
Section: Discussionmentioning
confidence: 88%
“…Resveratrol has shown in interfering with estrogen receptors, which is one way, has an indirect relation with diabetes (Li et al, 2018) . Has told above resveratrol effects in diabetes has already been researched in rats, which are made diabetic by streptozocin.…”
Section: Resveratrolmentioning
confidence: 99%
“…In a few studies, resveratrol has also shown to act on insulin resistant and increase insulin levels. Table 2 Resveratrol and 17β-estradiol 17β-Estradiol action in diabetes has already been proved along with resveratrol as discussed in various diabetic animal models (Catanuto et al, 2009;Li et al, 2018), in diabetic humans, and also in rats with Type 1 D. But estrogen has some interference in studies, so its effect was removed by removing both ovaries. Various parameters such as T-AOC (plasma total antioxidant capacity), FPI (Fasting Plasma insulin level), etc... were studied.…”
Section: Resveratrolmentioning
confidence: 99%